Potensi Minyak Atsiri untuk Mengendalikan Potyvirus pada Tanaman Nilam - Maya Mariana; Rita Noveriza (Jurnal Fitopatologi Indonesia, 2013)
One of the problems in the cultivation of patchouli is a mosaic disease caused by viruses. The dominant virus causing mosaic disease on patchouli plant belongs to Potyvirus group. Mosaic disease has spread throughout the central patchouli production in Java and Sumatra which can lower the wet herb, dried herb, oil and patchouli alcohol levels. The active contain of essential oils are reported as anti virus such as β - caryphyllene, thymol, carvacrol, caryophyllene oxide, sabinene, linalool, linaly acetate, carvone and geraniol. The research aims to determine the potential and concentration of essential oils that can suppress Potyvirus. The research used essential oil from clove and citronella. Oil was sprayed onto the leaves surface and left for 24 hr, then sap from Potyvirus infected plant was mechanically inoculated. Citronella oil concentration of 1.2 % have less number of lesions compared to the other treatments on the third day after inoculation. The percentage inhibition of citronella oil to Potyvirus on 1.2 % concentration reached 89.78 %. This showed that citronella oil has potential to suppress the development of Potyvirus in patchouli plant.Key words: antiviral, citronella oil, clove, mosaic disease